The role of laparoscopy in the diagnosis and management of pelvic adhesions involving the large bowel: a challenging case from a rural setting - Nditika, Elias; D., Njeri (International Surgery Journal, 2025)
Chronic pelvic and lower gastrointestinal symptoms often pose diagnostic difficulty, especially in resource-limited settings where advanced imaging and specialized surgical services are scarce. We report the case of a 76-year-old woman with a decades-long history of progressively narrowing stool caliber and left iliac fossa pain, for whom repeated colonoscopic and radiologic investigations failed to identify a cause. Diagnostic laparoscopy revealed extensive pelvic adhesions tethering the proximal rectum to the posterior uterus. Adhesiolysis resulted in marked symptomatic improvement. This case highlights the diagnostic utility and therapeutic role of laparoscopy in detecting adhesive bowel disease, particularly in rural centres. Strengthening minimally invasive surgical capacity in such regions can greatly improve outcomes for patients with chronic, unexplained gastrointestinal symptoms.